Improving Weekend Out Of hours Surgical Handover (WOOSH). Issue 1 (5th April 2016) - Boyer, Melissa; Tappenden, Janine; Peter, Mark
Abstract : An effective surgical handover is imperative to optimise patient care and safety, whilst ensuring progression of clinical management and the delivery of an efficient service. The introduction of full-shift working, as a response to progressive implementation of the European Working Time Directive (EWTD), has placed the spotlight on patient and doctor safety. Effective handover between shifts is vital to protect patient safety and assist doctors with clinical governance. The weekend is a critical point where the transfer of patient care to the ongoing weekend team is efficient, thorough and informative, as this is a point in the patient journey where the patient is the most vulnerable. The weekend team is often not responsible for the management of the patient throughout the week and poor or incomplete information can have disastrous consequences on patient safety. (1, 2, 3) There is a general consensus and anecdotal evidence that this process is variable, occasionally unsafe or of poor quality, and can be improved. (4, 5, 6, 7, 8, 9, 10, 11) However, no standardised format is deemed optimal or available. The aim therefore, was to design and implement a weekend handover proforma, in order to deliver a more efficient and safer system for patient care over the weekend without increasing junior doctor workload. The Weekend Out Of Hours Surgical Handover (WOOSH) form was designed following consultation with medical, nursing and allied health professionals. All staff were instructed how to complete the form, with pre- and post-intervention questionnaires undertaken. The results of the study enforce and advocate the permanent practice of the WOOSH form with 93.33% endorsing the permanent introduction of the form and 100% finding the form useful.